Corporate governance and firm performance in Korea / Hyo Jin Kim and Soon Suk Yoon - Kim, Hyo Jin (Accounting Research Institute (ARI) & Faculty of Accountancy, 2007)
We investigate how firm performance is related to corporate governance in Korea. We find that the adoption of an audit committee itself does not significantly improve the level of firm performance. However, we find that there is positive relationship between the outside directors' activity level and firm profitability. This suggests that outside directors can play a role of reducing agency conflicts between management and external shareholders so that the profitability is positively with their activity.